2002
DOI: 10.1007/s00572-001-0147-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phenanthrene and Rhodotorula glutinis on arbuscular mycorrhizal fungus colonization of maize roots

Abstract: The effect of the polycyclic aromatic hydrocarbon (PAH) phenanthrene and the yeast Rhodotorula glutinis on the arbuscular mycorrhizal fungus (AMF) Glomus geosporum colonizing maize roots, was studied. During a 90-day experiment, the highest G. geosporum colonization values were found in control plants. Mycorrhiza root length, measured both on the basis of percentage of root colonization and on the activity of succinate dehydrogenase, showed similar patterns in different phenanthrene treatments. The presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 15 publications
5
8
0
2
Order By: Relevance
“…At the highest PAH level of 200 + 200 mg kg −1 , the mycorrhiza infection rate was significantly (p < 0.05) lower than that of unspiked control (Table 1). This is in agreement with results of Gaspar et al [31], who found that there was a restriction of fungal hyphal growth in the presence of PHE. Cabello [32] also noted soil hydrocarbon contamination had negative effects on AMF-symbiosis, in terms of arbuscles percentage, vesicle number and entry point number.…”
Section: Effects Of Pahs and Pah-degrading Bacteria On Mycorrhiza Infsupporting
confidence: 92%
“…At the highest PAH level of 200 + 200 mg kg −1 , the mycorrhiza infection rate was significantly (p < 0.05) lower than that of unspiked control (Table 1). This is in agreement with results of Gaspar et al [31], who found that there was a restriction of fungal hyphal growth in the presence of PHE. Cabello [32] also noted soil hydrocarbon contamination had negative effects on AMF-symbiosis, in terms of arbuscles percentage, vesicle number and entry point number.…”
Section: Effects Of Pahs and Pah-degrading Bacteria On Mycorrhiza Infsupporting
confidence: 92%
“…Our results reveal a significant decrease of AMF root colonization in individual compartments due to local crude oil supply (Table 3). The observations are well in line with studies conducted with single polyaromatic hydrocarbons such as anthracene, phenanthrene or benzo(a)pyrene (Franco-Ramirez et al 2007;Gaspar et al 2002;Verdin et al 2006) or with industrial hydrocarbon deposits (Leyval and Binet 1998). p-values and means of the selected factor levels are generated by means of two-way ANOVA, based on the main factors "pollution" (two levels: C, P) and "mycorrhiza" (two levels: nM, M) a,b exponents display different levels of the main factor "pollution" a the conjugated compartment is filled with non-polluted control soil b the conjugated compartment is filled with polluted soil c,d exponents display different levels of the main factor "mycorrhiza" c the conjugated compartment is non-mycorrhizal d the conjugated compartment is inoculated with AMF Table 5 Statistical results on P. vulgaris developmental response to either "pollution" or "mycorrhiza", homogeneously or heterogeneously distributed in the split root system Reduced AMF root colonization may be influenced by diminished spore germination and reduced hyphal growth in the initial phase of root colonization.…”
Section: Root Colonizationsupporting
confidence: 85%
“…Following studies indicated that mycorrhizal fungal species could be affected and differ in their effect on the bacterial and fungal community composition in the rhizosphere (Paulitz and Linderman 1989;Pfleger and Linderman 1996;Godeas et al 1999;Marschner et al 2001;Gaspar et al 2002;Jeffries et al 2003;Marschner and Baumann 2003). Martı´nez et al (2004) repoted that Trichoderma pseudokoningii inhibited the germination …”
Section: Discussionmentioning
confidence: 99%